Formulation and Evaluation of Polyherbal Peel Off Mask - Lokhande, Shreya; Mankar, Shraddha; Satpute, Achal; Jadhao, Monika (Asian Journal of Pharmaceutical Research and Development, 2024)
When applied across the skin’s mucous membrane, skin care products including gel, lotion, ointment, cream, peel-off masks, etc., are meant to have a localised effect. A peel-off mask is a type of dosage form that is gently placed to the face and taken off after a short while. It is said to tighten, moisturise, and eliminate tan lines from the skin in addition to treating common skin problems. We are now preparing the recipe for a Tulsi peel-off face mask. Tulsi extract lessens acne, evens out skin tone, and slows down the ageing process of the skin. As excipients, the formulation includes glycerol, citric acid, and polyvinyl alcohol (PVA) etc. Numerous formulations were examined for peeling time, spreadability, pH, and stability studies, among other attributes. When evaluated for the parameters, the formulation is found to be within the designated range.